EKSISTENSI AGAMA TAO DAN PELAYANAN HAK-HAK SIPIL DI KOTA PALEMBANG - Suhanah Suhanah (Harmoni, 2015)
The study investigates the existence of Taoism and civil right services. This study employs qualitative approach and case study as the research methodology. The focus of the study provides Tao religion description consisting of the history, Tao principles and teachings, adherents and their spread, the government policy to fulfill Taoists’ civil rights, and social interaction between Taoists and other surrounding communities. The conclusion is Taoism still exists and gets the concessions from the goverment such as religious freedom to worship and recognition that can be seen from the establishment of Tao organization such as Paguyuban Umat Tao Indonesia (PUTI) and Majelis Tridharma Indonesia (MTI). Moreover, Taoists also obtain the civil rights such as services to get identity card, family register, marriage, and education. They get those services because they are under Buddhism scope. No one admits herself/himself as Taoist. The social interactions with other communities show good relationship. They have not had problem with others and goverment. They always comply the determined rules even though they have not had sufficient services.